BRCA2 mediates centrosome cohesion via an interaction with cytoplasmic dynein. Issue 16 (17th August 2016) - Malik, Sadiya; Saito, Hiroko; Takaoka, Miho; Miki, Yoshio; Nakanishi, Akira
Abstract : BRCA2 is responsible for familial breast and ovarian cancer and has been linked to DNA repair and centrosome duplication. Here we analyzed the mechanism by which the centrosomal localization signal (CLS) of BRCA2 interacts with cytoplasmic dynein 1 to localize BRCA2 to the centrosome. In vitro pull-down assays demonstrated that BRCA2 directly binds to the cytoplasmic dynein 1 light intermediate chain 2. A dominant-negative HA-CLS-DsRed fusion protein, the depletion of dynein by siRNA, and the inactivation of dynein by EHNA, inhibited the localization of BRCA2 at centrosomes and caused the separation of centrosome pairs during the S-phase. The double depletion of BRCA2 and C-Nap1 caused a larger dispersion of centrosome distances than the silencing of C-Nap1. These results suggest that cytoplasmic dynein 1 binds to BRCA2 through the latter's CLS and BRCA2 mediates the cohesion between centrosomes during the S phase, potentially serving as a cell-cycle checkpoint.